No More Suffering: Building Human Resource Capacities with the Sphere Standard. Issue Volume 34:Issue s1(2019) (May 2019) - Harada, Nahoko; Kai, Soichiro; Chishima, Kayako; Miyamoto, Junko; Kodama, Mitsuya; Koda, Masahide; Bando, Makoto; Tani, Hirofumi
Abstract : Introduction: Nankai Trough earthquake, with an anticipated death toll of 323, 000, is a disaster for which the country of Japan set the highest priority on building capacities. Tokushima prefecture aims to minimize preventable death among survivors and has strived to build a medical and health response system and strengthen outreach systems for vulnerable populations. To actualize these aims, Tokushima prioritized human resource development. Methods: Tokushima has initiated periodic trainings based on the Sphere Standard, the internationally recognized minimum standards for humanitarian aid, since 2015. The trainings were conducted by certified trainers and trainees received an official certification recognized by the Sphere Project, Geneva. The training materials were localized and the trainings were contextualized to Japan as a developed and super-aged nation. The learning outcome was evaluated by a pre-post test. Results: Between April 2015 and November 2018 the two-day training was held seven times. There were two hundred twelve participants from various clusters such as health, education, logistics, nutrition and food, security, and protection. The results of the pre-post test were statistically significant (still in process) indicating the effectiveness of the training on knowledge. Training evaluations suggest nurturing ethical attitudes and skills utilizing the Sphere Handbook. Discussion: Despite under-recognizing the Sphere Standard in Japan, the Standard has been incorporated into the disaster risk reduction plan in Tokushima. For larger scale human resource development, training local representatives to be trainers would be the next step.